Enhancing financial management practices for zakat micro-entrepreneurs in the new normal through impact- focused framework: a conceptual paper / Leylawati Joremi, Ruhaini Muda and Juliana Noor Kamaruddin - Joremi, Leylawati; Muda, Ruhaini; Kamaruddin, Juliana Noor (Universiti Teknologi MARA, 2021)
The zakat micro-entrepreneurs (ZME) programs aim to improve mustahiq’s (beneficiaries) standard of living and well-being. Its effectiveness depends on mustahiq’s wisdom in managing finances. The objective of this study is to conceptually discuss on the development of an impact-focused framework for the mustahiq using the financial management practices (FMP) as a quality intervention program. The research framework of this study is built on the Theory of Change and Logic Model that posited quality of intervention contributes to a series of outcomes and intended impact. This study discusses three propositions. First, the best FMP as a quality intervention for the ZME. Second, a social impact measurement framework for ZME programs and third, the description of the data collection application using mixed-methods for the proposed framework. The outcomes of this study will benefit zakat institutions in evaluating the effectiveness of zakat funds in improving the well-being of the mustahiq.